The Role of the Signaling Pathways Involved in the Effects of Hydrogen Sulfide on Endoplasmic Reticulum Stress - Zhao, Shizhen; Li, Xinping; Lu, Ping; Li, Xiaotian; Sun, Mingfei; Wang, Honggang (Frontiers in Cell and Developmental Biology, 2021)
Endoplasmic reticulum (ER) is a kind of organelle with multiple functions including protein synthesis, modification and folding, calcium storage and lipid synthesis.Under stress conditions, ER homeostasis is disrupted, which is defined as ER stress (ERS).The accumulation of unfolded proteins in the ER triggers a stable signaling network named unfolded protein response (UPR).Hydrogen sulfide is an important signal molecule regulating various physiological and pathological processes. Recent studies have shown that H2S plays an important role in many diseases by affecting ERS, but its mechanism, especially the signaling pathways, is not fully understood. Therefore, in this review, we summarizes the recent studies about the signaling pathways in the effects of H2S on ERS in diseases to provide theoretical reference for the related in-depth researches.